Local and Organic Preference: Logo versus Text. (8th April 2019) - Katz, Michael; Campbell, Benjamin; Liu, Yizao
Abstract: A choice experiment was conducted concurrently with eye-tracking technology to examine consumer preferences for local and organic produce, notably effects of logo- versus text-labeling formats. We find consumers prefer local to nonlocal, but some consumers will pay a higher premium for logo-labeled produce compared with text-labeled produce. Additionally, we find evidence that a local logo tends to attract attention quicker and hold attention longer compared with a text label. The organic text label was preferred by some consumers compared with the USDA certified organic logo, even with though consumers looked at the logo longer and more often.